Hygrometrically controlled programmed cell death drives anther opening and pollen release - Anna Kampová; Moritz K. Nowack; Matyáš Fendrych; Stanislav Vosolsobě (Proceedings of the National Academy of Sciences, 2025)
Anther dehiscence is the process that facilitates pollen release from mature anthers in flowering plants. Despite its crucial importance to reproduction, the underlying developmental mechanism and its integration with environmental cues remain poorly understood. Establishing noninvasive, controlled humidity treatments of Arabidopsis thaliana flowers, we show here that high humidity prevents anthers from opening. Manipulation of stomatal densities alters dehiscence dynamics, suggesting a contribution of controlled transpiration. Furthermore, analyses of subcellular markers revealed the occurrence of a developmentally prepared and environmentally triggered programmed cell death (PCD) process in specific anther tissues, epidermis and endothecium. Notably, genetic inhibition of PCD delays anther dehiscence, whereas precocious PCD induction promotes it. Our data reveal a rapid PCD execution process modulated by ambient humidity as instrumental for timely pollen release in the flowering plant Arabidopsis .